Anterior dislocation of sternoclavicular joint: A novel surgical technique. Issue 4 (April 2022) - Fandridis, Emmanouil; Koutserimpas, Christos; Raptis, Konstantinos; Antonopoulos, Dimitrios; Zampeli, Frantzeska; Gakidis, Ioannis
Abstract: Introduction: Anterior sternoclavicular joint dislocation (SCJ) is a relative rare injury, related to high energy trauma. The objective of the present study is to present a novel suture technique for treatment of anterior SCJ traumatic dislocation and to report clinical outcomes from a small case series undergoing this procedure. Patients and Methods: Patients presenting with traumatic anterior SCJ disruption in our institution were eligible to participate. Surgical technique consisted of two bone tunnels drilled in vertical direction from the anterior to the posterior cortex of the manubrium. Analogous to the sternal side of the clavicle, two vertical bone tunnels were drilled from the anterior cortex towards the posterior cortex. A non-absorbable suture was passed though the four holes in a parallel configuration. Then, by pulling the free suture edges the posterior translation of the clavicle was performed. Two additional drill holes, the first in manubrium and the second in clavicle were performed from the anterior cortex to the posterior between the previous bone tunnels. A non-absorbable suture was placed in a simple configuration in order to stabilize the SCJ in the superior–inferior direction. The final follow up was 28.2 months. The mean QuickDASH was used for functional assessment. Results: Seven patients (6 males and 1 female) with average age of 34, 8 years were included in the present study. Two patients suffered from concomitant medial clavicle fracture. At final follow-up (none of the patients had experienced any symptoms of instability of SCJ, no side-to-side difference was observed, while the Mean QuickDASH score was 4.85. Conclusion: The reported technique for SCJ reconstruction in traumatic anterior SCJ dislocations with two sutures has theoretical advantages, since it stabilizes the SCJ in the antero–posterior, as well as the supero- inferior direction. Outcomes from this small case series are favorable. However, more research is desirable to compare different techniques and to conclude to the optimal surgical treatment.